Analisis Pertumbuhan Wilayah Dan Perubahan Lahan Terhadap Pengembangan Fungsi Jalan Di Kelurahan Bencah Lesung Kecamatan Tenayan Raya kota Pekanbaru - Roro Wilis Irene; Rian Tri Komara; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The aims of this paper is to examine the influence of the landuse changing towards traffic generation on Hangtuah street’s corridor in Pekanbaru city. The object that to attained are to identification the condition of landuse and transportation , calculate the traffic flow (traffic counting) for each landuse, analyze the development of the landuse, analyze the trip generation, and analyze the influence of the landuse changing towards traffic generation on Hangtuah street’s corridor in Bencah Lesung subdistrict in Pekanbaru city.The research method that used in this paper is descriptive that identification landuse condition and transportation at Hangtuah street. Then, performed analysis of landuse’s development, analysis of generation and attraction, and analysis of the influence of landuse towards generation and attraction of Street of Hangtuah street in Bencah Lesung Subdistrict in Pekanbaru city.Keywords: landuse, traffict, transportation